Implementation Of Two-way Free Space Quantum Key Distribution - Mohd Fared Abdul Khir; Mazainun A. Mohd Zain,; Suhairi Saharudin,; Suryadi Soekardjo,; Sahbudin Bin Haji Shaari (Society of Photo-Optical Instrumentation Engineers, 2024)
We report an implementation of a two-way, four-state quantum key distribution (QKD) protocol (namely, the LM05 protocol) over a free space medium. A stable quantum bit error rate of 3.34% and maximum tolerable channel loss for secure key generation of 5.68 dB in the absence of a photon number splitting attack were recorded. The result strongly indicates the feasibility of a two-way QKD protocol implementation over a free space medium.